Manajemen Hubungan Stakeholder Dalam Peningkatan Mutu Pendidikan Di Madrasah - Indriyani Keliawawa; Nadia Rahmadani; Sulis Maryati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This article discusses stakeholder relationship management in developing educational quality in madrasas. The study focuses on how madrasas build communication, participation, partnerships, and joint evaluation with stakeholders, such as principals, teachers, students, parents, madrasa committees, the community, the government, and the business world. The method used is a literature study by reviewing scientific journals, books, and relevant educational regulations. The results of the study indicate that developing madrasah quality is not sufficient through internal improvements but needs to be supported by targeted, transparent, participatory, and sustainable stakeholder relationship management. Stakeholder relationship management serves as a strategy to unify vision, strengthen resource support, increase accountability, and build a quality culture based on Islamic values. The main challenges faced include differences in interests, weak communication, low participation, limited resources, and the suboptimal use of digital technology. Therefore, madrasas need to develop a stakeholder relationship pattern based on deliberation, trust, collaboration, and quality evaluation to be able to produce superior, relevant, and competitive educational services.